EVALUASI KEBERHASILAN INSEMINASI BUATAN PADA SAPI POTONG DI KECAMATAN PAMMANA KABUPATEN WAJO - Andi Mutmainna (Jurnal Peternakan (Jurnal of Animal Science), 2020)
Artificial insemination (AI) has served as appropriate technology for ameliorating quality and population of cattle using superior male. Our present work aimed to evaluate AI service in District of Pammana, located in Regency of Wajo. Field survey and interview with inseminators were carried out to collect primary data, while secondary data was obtained from local government authority, i.e. department of food security and animal husbandry. The research investigated 320 acceptors during January – December 2020. Collected data was then descriptively analysed, while other parameters, i.e. service per conception (S/C) and conception rate (CR), were also assessed to evaluate AI efficiency. As the results, AI service in Pammana has been properly performed, as indicated by number of acceptors within 12 months. The inseminated acceptors in Pammana reached S/C score of 1.78 and CR of 60.37%, in which both indicators are rated as good. Male calf being born following AI was was more dominant (321) in comparison with female calf (283), with total calves born reaching 604.